2019
DOI: 10.1039/c9ra01914f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on strength development of lime stabilized loess

Abstract: Lime stabilization has been widely used in pavement subbases and ground improvement, but the investigation of the mechanical properties and the microstructure of lime stabilized loess is still insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The dry density was controlled to be 1.58, 1.48, and 1.38 g/cm 3 for the lime stabilized loess specimens at points C, D, and E. Moreover, the specimens at point D were prepared with three different lime percentages: 10%, 16% and 23% to investigate the effects of lime content on its strength behavior. 14 The molding points for the triaxial compression tests are summarized in Table 3. Combining with the experimental procedure of Consoli et al [34] and the results of the standard compaction test, 5 molding points (A, B, C, D and E) were set in this study.…”
Section: Standard Compaction Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry density was controlled to be 1.58, 1.48, and 1.38 g/cm 3 for the lime stabilized loess specimens at points C, D, and E. Moreover, the specimens at point D were prepared with three different lime percentages: 10%, 16% and 23% to investigate the effects of lime content on its strength behavior. 14 The molding points for the triaxial compression tests are summarized in Table 3. Combining with the experimental procedure of Consoli et al [34] and the results of the standard compaction test, 5 molding points (A, B, C, D and E) were set in this study.…”
Section: Standard Compaction Testmentioning
confidence: 99%
“…However, these bonds can break down after immersing in water or applying a greater stress, which can result in the collapse and deformation of the structure [4]. Furthermore, it may even lead to serious geotechnical disasters, such as uneven settlement of the foundation, landslides and ground fissures [5][6][7][8], and has thus attracted attention from scientists and engineers worldwide [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ni [ 8 ], Xu [ 9 ] and Ge M [ 10 ] compared the changes of loess microstructure before and after permeability test by SEM. Jwa [ 11 ], Jia [ 12 ] analyzed the changes of loess microstructure in tensile and infinite lateral compression tests, respectively. Above results suggested that the structure had an important influence on the mechanical deformation properties of loess [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research results indicated that the application of stabilizing agent (such as cement or lime) can significantly improve the mechanical properties of soft soils [16][17][18][19]. The addition of lime has been a popular solution for loess stabilization, due to low cost and high technical efficiency in engineering applications [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…With an appropriate proportion of lime and slag used in the soil mixture, the early Table 1. Physical properties of the natural loess [19].…”
Section: Introductionmentioning
confidence: 99%